Assessing the health of sensors using data historians - Eren, Halit (IEEE, Piscataway, NJ, USA, 2012)
This paper suggests and investigates a new method of determining the health of sensors by using of the information in the data historians commonly used in process control applications. This method allows validation and reconciliation data to account for incomplete or conflicting measurements coming from the sensors under normal operational process conditions. The aim is to compare the historical data with the live data to assess the health of any and every sensor in the process anytime and every time. Experiments are set up in PLC/SCADA environment to test the integration of the live and historical data, thus indication some encouraging results.